Analisis Perubahan Borrow Area Material Inti Terhadap Harga Satuan Pekerjaan Timbunan pada Proyek Pembangunan Bendungan Jragung, Kabupaten Semarang - Ima Fisriyanto; Muhammad Zaki (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the effect of changes in the borrow area of core material on the unit price of embankment work in the Jragung Dam Project, Semarang Regency. The research employed a quantitative-descriptive approach using primary data from soil laboratory test results and secondary data obtained from project documents. Samples were selected through purposive sampling from three borrow area locations with a total of 15 testing points. The analysis involved technical and economic evaluations of material suitability, volume availability, and the impact of borrow area changes on construction costs. The results showed that the initial borrow area material did not meet technical specifications and experienced a volume shortage of 294,896.45 m³ due to gravel content, tuffaceous layers, and organic soil. An alternative material source from Gunung Mergi, located 23–25 km from the project site, was selected and met the required technical specifications. However, the change in material source increased the unit price of embankment work from IDR 115,860.00 to IDR 248,478.00 due to longer hauling distances and additional material management requirements, including stockpile utilization to maintain moisture content. The novelty of this study lies in integrating technical material suitability, volume availability, and economic impacts of borrow area changes within a single evaluation framework. The findings provide a practical basis for material source selection, risk management of borrow area changes, and more accurate cost estimation in dam construction projects.